Compósito de argamassa de cimento reforçada por fibra de sisal com entalhe definidos: caracterização mecânica e mecanismo de falha - PERES, Maria das Neves Pontes Barata (Universidade Federal do Pará, 2014)
In this work, we developed a new composite material using as a matrix of cement mortar reinforced with sisal fibers to 1% by weight, which were manually cut into lengths of 15 mm and 25 mm used without surface treatment using the lowest possible level of technological processes in manufacturing steps. The research was conducted to study the mechanisms of failure of this new material. The composites were produced with manual molding using immersion vibrator for better densification. Specimens were fabricated of the pure base and with the composites with sisal fiber, with pre-defined slots of 1.7 mm, 3,0 mm and 5,0 mm. The mechanical properties were evaluated by a bending test at three points and correlated with the fractographic appearance made in the Scanning Electron Microscope. The results showed that the presence of sisal fibers, embedded in cement paste,plastic shrinkage caused restriction of fresh mixture, possibly due to high water absorption capacity of fibrous reinforcement, an increase in mechanical strength and increased toughness of the composite over the base between the series of notches, decreasing the tendency to sudden fracture.